1999
DOI: 10.1080/02607479919673
|View full text |Cite
|
Sign up to set email alerts
|

Choosing Primary Teaching as a Career: The perspectives of males and females in training

Abstract: This paper is set in the context of concern about the decline in the numbers of males entering the primary teaching profession in the United Kingdom and focuses on the views of male and female primary teacher trainees as to the factors which in¯uenced their decision to enter the teaching profession. Findings of this study reveal that females in training claim to have been motivated by the perceived intrinsic aspects of primary teaching whereas place a greater emphasis on perceived extrinsic aspects. Males in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
2
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(55 citation statements)
references
References 4 publications
5
43
2
5
Order By: Relevance
“…(Female PGCE) Like other researchers in the field (Smedley, 1999;Johnston et al, 1999), we found that issues relating to the gender of the teacher were of far greater concern for men in 1998, at the start of their training, than they were for women, and that men more frequently expressed concerns about pupil behaviour than did women.…”
Section: Concerns About Becoming a Teacher In 1998mentioning
confidence: 56%
“…(Female PGCE) Like other researchers in the field (Smedley, 1999;Johnston et al, 1999), we found that issues relating to the gender of the teacher were of far greater concern for men in 1998, at the start of their training, than they were for women, and that men more frequently expressed concerns about pupil behaviour than did women.…”
Section: Concerns About Becoming a Teacher In 1998mentioning
confidence: 56%
“…It is also interesting, though not incomprehensible, the fact that both male and female reviewees believe that it is more difficult for women to retain a balance between professional advancement and family duties (Acker, 1992;Casey, 1990;Cinamon & Rich, 2005). It seems, in fact, to be a plain description of Greek social reality, where women seemingly have the same professional rights and opportunities as their male colleagues do, although, in practice, the double role of being a parent and a professional at the same time hinders women more than men (Hewlett, 2002;Mason & Mason-Ekman, 2007) due to the obstructive combination of existing social stereotypes and the lack of institutional support to motherhood (insufficient number of public nursery schools and kindergartens, insufficient children and parent health care, low family allowances, insufficient teacher salary and so on) (Hargreaves, 1994;Johnston et al, 1999).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Z doterajších výskumov, v oblasti motivácie voľby výkonu povolania učiteľa, škála indikuje existenciu 11 (osem vo verzii SMVUP-S a SMVUP2-S; Tomsik, 2015b) typov motivácie voľby učiteľského povolania: kompetencie (BookFreeman, 1986;Robertson -Keith -Page, 1983;Skatova -Ferguson, 2014), záujem (Watt, et al 2012;Kasacova, 1996), benefity (Kyriacou -HultgrenStephens, 1999;Johnston -McKeown -McEwen, 1999;Watt -Richardson, 2007), príjem (Şahin, 2014;Papanastasiou -Papanastasiou, 1997;Saban, 2003), sociálny status (Yong, 1995;Chivore, 1988;Bastick, 1999), prosociálne správanie (Hrebicek, 1995;Johnston -McKeown -McEwen, 1999;Kyriacou -Hultgren -Stephens, 1999), práca s deťmi, práca s mladistvými (Watt -Richardon, 2012, 2013Saban, 2003;Tomsik, 2016), alternatívna voľba povolania, ovplyvnenie inými (Fresko -Kfir -Nasser, 1997;Karikova, 2004;Sparkes, 1988) a celoživotné vzdelávanie (Hrebicek, 1995;Tomsik -Veresova, 2016). Prvá reedícia SMVUP-S výskumného nástroja (SMVUP2-S) publikovaná v prvom kvartáli roku 2016 obsahovala 37 položiek, ktoré boli redukované, na základe exploračnej faktorovej analýzy, na 32 položky.…”
Section: Charakteristika a Konštruktová Validita Smvup3-sunclassified